Antimicrobial activity of some medicinal plants of the Cerrado, Brazil - Costa, E. S.; Hiruma-Lima, Clélia Akiko [UNESP]; Lima, E. O.; Sucupira, G. C.; Bertolin, A. O.; Lolis, S. F.; Andrade, F. D. P. [UNESP]; Vilegas, Wagner [UNESP]; Souza-Brito, A. R. M. (John Wiley & Sons Ltd, 2008)
In order to determine the potential of Cerrado plants as sources of antimicrobial activity, the phytochemical screening of ethanol extracts from Virola surinamensis, Qualea grandiflora, Alchornea castaneifolia, Hancornia speciosa and Curatella americana traditionally used in folk medicine are reported. Copyright (C) 2008 John Wiley & Sons, Ltd.
Keywords: antimicrobial activity; Qualea grandiflora; Alchornea castaneaefolia; Curatella americana; Virola surinamensis; Hancornia speciosa